Antifungal Activity of Leaf Extracts of Some Plant Species on Mycosphaerella fijiensis Morelet, The Causal Organism of Black Sigatoka Disease in Banana (Musa acuminata) - Okigbo, R.N.; Emoghene, A.O. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The effect of leaf extracts of Vernonia amygdalina Del., Azadiracta indica A. Juss and Ocimum gratissimum L. on conidiospore germination, mycelia extension and lesion development of Mycosphaerella fijiensis Morelet, the casual agent of black Sigatoka disease of banana was investigated. An increased antifungal activity was noticed with a corresponding increase in concentration of aqueous extracts from all the plants. A 100% concentrated extract of O. gratissum completely inhibited conidial germination (P<0.05). There was a general decrease in the incidence of lesion occurrence on all the banana plants sprayed with plant extracts in the field in a descending order of O. gratissimum, A. indica and V. amygdalina. Extracts of O. gratissimum compared favourably with the disease control achieved with benomyl application. These findings are discussed in relation to plant chemical means of disease control on banana. Keywords: Mycosphaerella fijiensis, black Sigatoka, banana, plant extracts, plant disease control, antifungal activity. Corresponding author: E-mail: okigborn17@yahoo.com